Performance Recovery Following Upward and Downward Flushing of Up-flow Sand Filter - Farhana Abd Lahin; Abigail Bernardette Yong; Rosalam Sarbatly (ASEAN Journal of Chemical Engineering, 2024)
The up-flow sand filter (USF) is an excellent alternative to conventional downward sand filters, reducing susceptibility to clogging. Two methods of cleaning the USF are upward flushing and downward flushing. The efficiency of both methods towards water quality was investigated by comparing the recovery of turbidity, total suspended solids (TSS), dissolved oxygen (DO), and pressure drop. The results obtained after upward flushing include turbidity levels of 22.64 NTU, TSS levels of 33.13 mg/L, DO levels of 4.78 mg/L (top layer), 5.20 mg/L (middle layer), and 4.20 mg/L (bottom layer), as well as a pressure loss recovery difference of 6.05 cm. Meanwhile, downward flushing obtained turbidity levels of 27.84 NTU, TSS levels of 34.5 mg/L, DO levels of 6.12 mg/L (top level), 6.38 mg/L (mid-level), and 5.48 mg/L (bottom level), as well as a pressure drop recovery difference of 12.87 cm. The ripening period of a filter refers to the stage where the sand filter matures and reaches its optimum filtration ability. In this research, the ripening period achieved after upward flushing was 11 hours, while after downward flushing was 8 hours. This was obtained by measuring the time it took for water parameters to stabilize after flushing. Overall results showed that upward flushing was more efficient due to higher turbulence during upward flushing, allowing contaminants to dislodge from gaps or surfaces of sand particles.